Implementation, innovation or incremental change? Analyzing 25 Danish municipalities’ translation of the Dutch Buurtzorg Model for home care - Topholm, Emmy Hjort-Enemark; Møller, Anne Mette; Buch, Martin Sandberg (Politica, 2025)
Danish municipal elderly care is facing significant challenges, including recruitment issues. Inspired by the successful Dutch Buurtzorg model, central government has allocated funds to support local innovation. Based on translation theory and grounded in 50 qualitative interviews involving 159 individuals in 25 municipalities, this article analyzes how the Buurtzorg model is translated in a Danish elderly care context. On a policy level, Buurtzorg is translated from a complex organizational model into an idea of permanent, interdisciplinary and self-managing teams. Municipalities’ local translations of these core elements encounter challenges, including resistance from frontline workers and unchanged framework conditions. This results in significant variation but relatively minor changes, indicating incremental change rather than innovation, and raises the question of how central government can best support local innovation.